Implementasi AI (ChatGPT) dalam Pengerjaan Tugas Mahasiswa - Fitri, Rossa (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2024)
: This research aims to analyze the implementation of AI (ChatGPT) in the field of education, especially among students. This issue is interesting to discuss because, with technological advances, the use of AI is no longer foreign to society. This research was conducted to answer the question of the impact of using AI (ChatGPT) in student assignments. The method used in this research is a qualitative method based on a literature review or library research. Based on the analysis, the use of AI can help students do their assignments, but on the one hand, it can also cause feelings of laziness and dependency. This thesis statement supports research from Widya Rizky Pratiwi, which revealed that AI helps students do their assignments by identifying quoted material and grammatical errors. The opposing opinions came from Sofi Liza Zahara, Zahira Ula Azkia, and Muhammad Minan Chusni, who revealed that there were negative impacts of implementing artificial intelligence in the education sector, including: 1) making teachers and students lazier; 2) eliminating some of the work of educators, especially in the administrative field; 3) AI cannot understand the purpose and information created; and 4) AI works according to what has been programmed.